Penyimpangan Seksual sebagai Alasan Terjadinya Perceraian Menurut Pengadilan Agama Cibinong: - Izwar Alhifni; Yono Yono; Mukhtar Mukhtar (Fakultas Syariah IAIN Laa Roiba Bogor, 2022)
Sexual deviation as a reason for divorce has given a negative and ambiguous stigma to society, especially to the views of judges and Islamic law based on these factors which are the study of sexual deviation as a reason for divorce. Therefore this research is entitled: Sexual Deviance As the Reason for Divorce According to PA Cibinong. The formulation of the problem from this research is to answer (1) What are the factors causing divorce in the Cibinong Religious Court, (2) What is the Judge's view on sexual deviation as a reason for divorce, (3) What is the view of Islamic Law on Sexual Deviance as a reason occurrence of divorce. The method used in this research is descriptive qualitative which is carried out to find out what the views of Islamic law on sexual deviance are as well as the impact that occurs due to sexual deviant behavior on marriage. This study uses primary data, namely observations in an object, interviews and secondary data sourced from Case Number: 5318/Pdt.G/2018/PA.Cbn, documents, books, and so on that are related to this research. The results of this research with factors that cause sexual deviance are due to weak faith, unable to contain lust, and the arrival of this aspect in almost every aspect of modern life that grows and develops not on the basis of the concept of religion. sexual intercourse without regard to the satisfaction of the opposite sex and in practice it is often accompanied by violence (hitting, kicking, etc.) which results in injury to the partner. So according to the Cibinong Religious Court Judge when viewed from PP No. 9 of 1975 Article 19 of this Sex Deviance can be categorized as a reason for divorce, in point d of the article it is explained, ie one party commits cruelty or severe abuse that endangers the other party in general about sexual violence in the household, and sexual deviance in particular is a new reason that is used as a reason for divorce before the court. without paying attention to the satisfaction of the opposite sex and not infrequently in practice it is spiked by violence (hitting, kicking, etc.) which results in injury to their partner. So according to the Cibinong Religious Court Judge when viewed from PP No. 9 of 1975 Article 19 of this Sex Deviance can be categorized as a reason for divorce, in point d of the article it is explained, that is, one party commits atrocities or severe abuse that endangers the other party in general about sexual violence in the household, and sexual deviance in particular is a new reason that is used as a reason for divorce before the court. Sexual violence in the household or sexual irregularities in the household that are widely used as reasons for divorce are physical violence, such as beatings, economic violence, in terms of economic neglect. Meanwhile, psychological violence and sexual deviations are rarely revealed in court. Unless these two types of deviation are simultaneously experienced by victims with physical violence. Keywords: Court, Judgment, Deviant Factors